PENGARUHPENERAPANMETODESTORYTELLINGBEBANTUANMEDIA ALAT PERAGATERHADAPHASILBELAJARPESERTADIDIKDIKELASV MIN 10BANDARLAMPUNG - Dewi Rahayu; Nur Asiah; Yuli Yanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Learning in elementary schools required creative and innovative strategies to helpstudents understand concepts concretely and meaningfully. One methodconsidered effective was storytelling, especially when combined with visual aidsthat were engaging and relevant to the learning material. This study aimed todetermine the effect of using the storytelling method assisted by visual aids on thelearning outcomes of fifth-grade students at MIN 10 Bandar Lampung. Theresearch employed an experimental approach with a quasi-experimental designusing the nonequivalent control group design. The subjects consisted of twoclasses: an experimental class (35 students) that used the storytelling methodassisted by visual aids and a control class (34 students) that applied the ProjectBased Learning (PjBL) method. Learning outcome data were collected throughtests and analyzed using the independent sample t-test with the help of SPSSsoftware. The results of the analysis showed that the Sig. (2-tailed) value was0.000 < 0.05, indicating a significant difference between the learning outcomes ofthe experimental and control classes. Therefore, the storytelling method assistedby visual aids was proven to be more effective in improving students’ learningoutcomes than the PjBL method. These findings confirmed that the combination ofnarrative and concrete media could enhance students’ motivation, attention, andconceptual understanding comprehensively. Hence, teachers were encouraged toimplement this method as an innovative and enjoyable alternative for elementaryschool learning.